2016
DOI: 10.1002/jaal.503
|View full text |Cite
|
Sign up to set email alerts
|

“Seeing It From a Different Light”

Abstract: Although research emphasizes the importance of reflection for productive learning, much of this work has focused on writing as the preferred mode. The goal of this study was to examine how two adolescent composers reflected on their multimodal visions and processes through multimodal means—in particular, how the students remixed research‐provided screen capture video, class observation video, and their multimodal products to each create a composer's cut video reflection. A multimodal matrix analytic approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…There has been an upsurge in studies examining how students utilise multiple modes when composing digital narrative texts (e.g. Dalton et al, 2015;Smith & Dalton, 2016), yet little is known about how students attend to multimodality when reading narratives in digital spaces. In previous research (Coiro & Dobler, 2007), skilled readers of traditionally printed texts provided important insights to the field of teacher education about engaging with informational texts in digital environments.…”
Section: Implications For Theory Policy or Practicementioning
confidence: 99%
“…There has been an upsurge in studies examining how students utilise multiple modes when composing digital narrative texts (e.g. Dalton et al, 2015;Smith & Dalton, 2016), yet little is known about how students attend to multimodality when reading narratives in digital spaces. In previous research (Coiro & Dobler, 2007), skilled readers of traditionally printed texts provided important insights to the field of teacher education about engaging with informational texts in digital environments.…”
Section: Implications For Theory Policy or Practicementioning
confidence: 99%
“…Previous research has suggested that adolescents' multimodal composing processes are complex and vary based on the convergence of multiple factors. Adolescents often exhibit unique modal preferences (Smith, 2016;Smith & Dalton, 2016), relying on modes in different ways to make meaning. For example, some students might prefer to initiate their multimodal composing process by focusing on visuals first, whereas other students might want to lay a written foundation before attuning to nonprint modes (Smith, 2016).…”
Section: Freedom In the Composing Process And Use Of Digital Toolsmentioning
confidence: 99%
“…For example, some students might prefer to initiate their multimodal composing process by focusing on visuals first, whereas other students might want to lay a written foundation before attuning to nonprint modes (Smith, 2016). By providing choices in the multimodal composition process, students learn how different modes possess unique affordances for communicating their message (Smith & Dalton, 2016). Students had the latitude to select which digital tools and online programs to use for creating their projects.…”
Section: Freedom In the Composing Process And Use Of Digital Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Have students create a Composer's Cut of their own digital writing (see Smith & Dalton, 2016). Students can record over their digital texts to explain their compositional choices and share how their own digital mentor texts influenced their digital compositions.…”
mentioning
confidence: 99%